2010
DOI: 10.1111/j.1537-2995.2009.02447.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune hemolytic anemia due to cimetidine: the first example of a cimetidine antibody

Abstract: This is the first reported case of IHA due to a cimetidine antibody where a drug-dependent antibody was demonstrated. The patient had IHA after receiving cimetidine on two separate occasions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Several studies have reported cases of cimetidine-induced immunohemolytic anemia. However, only one patient was serologically confirmed to be a case of DIIHA caused by cimetidine-dependent antibodies ( 24 ). The ability of oral cimetidine to elicit the production of cimetidine-dependent antibodies and consequently cause DIIHA has not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported cases of cimetidine-induced immunohemolytic anemia. However, only one patient was serologically confirmed to be a case of DIIHA caused by cimetidine-dependent antibodies ( 24 ). The ability of oral cimetidine to elicit the production of cimetidine-dependent antibodies and consequently cause DIIHA has not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…To coat the RBCs, the RBCs are incubated with 40 mg/mL drug solution at 37°C for 1 h (except for preparing penicillin-coated RBCs). However, Arndt et al ( 24 ) reported that the incubation of RBCs with 40 mg/mL cimetidine at 37°C for 1 h resulted in severe hemolysis and that this method does not yield a sufficient number of cimetidine-coated RBCs that can be used to detect cimetidine-dependent antibodies. Hence, cimetidine-coated RBCs were prepared by incubating RBCs with 15 mg/mL cimetidine at room temperature for 1 h. These RBCs did not undergo hemolysis and can be used to detect cimetidine-dependent antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cimetidine, which was supplied as an aqueous solution containing alcohol, hemolyzed RBCs when prepared at 40 mg/mL at both 37°C and room temperature, but was used successfully at 15 mg/mL in PBS with a room temperature treatment incubation. 23 For whatever method is used, another aliquot of RBCs is prepared under the same conditions in the appropriate buffer or PBS (without the drug) to serve as the control untreated RBCs. These untreated RBCs are tested in parallel with the drug-treated RBCs.…”
Section: Preparing Drug-treated Rbcsmentioning
confidence: 99%
“…For example, cimetidine-treated RBCs were nonreactive after storage overnight at 4°C. 23 Testing Drug-Treated RBCs Drug-treated RBCs are tested in parallel with the control untreated RBCs by tube test. Two sets of tubes are labeled for each sample to be tested.…”
Section: Preparing Drug-treated Rbcsmentioning
confidence: 99%